Efficiency and energy modelling for PVT air collector with extended heat transfer area: a review - Fudholi, Ahmad; Fazleena Musthafa, Mariyam; Taslim, Ivan; Ayu Indrianti, Merita; Noviantari Manyoe, Intan; Yusof Othman, Mohd (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Solar energy is renewable and environment friendly and has been widely used in electricity generation and thermal energy through photovoltaic thermal (PVT) system. This system is beneficial in terms of maximum energy generation and cost of usage. The growing concern on energy sources and their usage has increased the significance and demand for PVT collectors. A PVT air collector consists of a PV panel and a thermal collector system. In PVT air collector, electricity and thermal energy are generated simultaneously. This review focuses on efficiency and energy modelling for PVT air collector with extended heat transfer area. Findings of this review indicated that PVT air collector with extended heat transfer area produced PVT efficiency higher than conventional PVT air collector. The thermal efficiency of PVT air collector for with and without extended heat transfer area are 21-83% and 12-70%, respectively, which the improvement of thermal efficiency is 15.7-42.8%.